Sow environment during gestation: part I. Influence on maternal physiology and lacteal secretions in relation with neonatal survival. (23rd November 2018) - Merlot, E.; Pastorelli, H.; Prunier, A.; Père, M.-C.; Louveau, I.; Lefaucheur, L.; Perruchot, M.-H.; Meunier-Salaün, M. C.; Gardan-Salmon, D.; Gondret, F.; Quesnel, H.
Abstract : In pig husbandry, pregnant females are often exposed to stressful conditions, and their outcomes on maternal and offspring health have not been well evaluated. The present study aimed at testing whether improving the welfare of gestating sows could be associated with a better maternal health during gestation, changes in the composition of lacteal secretions and improvement in piglet survival. Two contrasted group-housing systems for gestating sows were used, that is, a French conventional system on slatted floor (C, 49 sows) and an enriched system using larger pens on deep straw (E, 57 sows). On the 105 th days of gestation (DG105), sows were transferred into identical farrowing crates on slatted floor. Saliva was collected from all sows on DG35, DG105 and DG107. Blood samples were collected on DG105 from all sows and on the 1 st day of lactation (DL1) from a subset of them (C, n =18; E, n =19). Colostrum and milk samples were collected from this subset of sows at farrowing (DL0) and DL4. Saliva concentration of cortisol was greater in C than in E sows at DG35 and DG105, and dropped to concentrations comparable to E sows after transfer into farrowing crates (DG107). On DG105, plasma concentrations of haptoglobin, immunoglobulins G (IgG) and A (IgA), blood lymphocyte counts and plasma antioxidant potential did not differ between groups ( P > 0.10), whereas blood granulocyte count, and plasma hydroperoxide concentration were lower in E than in C sows ( P < 0.05). Concentrations of IgG and IgA in colostrum and milk did not differ between the two groups. The number of cells did not differ in colostrum but was greater in milk from E than C sows ( P < 0.05). Pre-weaning mortality rates were lower in E than C piglets (16.7% v . 25.8%, P < 0.001), and especially between 12 and 72 h postpartum ( P < 0.001). Plasma concentration of IgG was similar in E and C piglets on DL4. In conclusion, differences in salivary cortisol, blood granulocyte count and oxidative stress markers between groups suggested improved welfare and reduced immune solicitation during late gestation in sows of the E compared with the C system. However, the better survival observed for neonates in the E environment could not be explained by variations in colostrum composition.